STUDENTS' PERSPECTIVE OF USING ROLE PLAY TO DEVELOP SPEAKING SKILL - Almira Mulyana (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2020)
This research was aimed know how was speaking skill was developed through a method based on students’ perspective. This was a qualitative design study by giving a questionnaires , interview, and observation to the English Department students. The data were collected from sixteen students from Faculty of Education majoring English Education at Ibn Khaldun Bogor University. The aims of this research is to find what the students’ perspective of role play method and what the effect that they felt from the method after they learned it. The instrument of this research is questionnaires form made in Google form. The data were analyzed by the researcher and the result of the research showed that more than 80% of Ibn Khaldun Bogor University students majoring English Department agree that Role Play method can be a fun method of learning to develop students' speaking skill. They conclude that role play has many positive impact on their speaking skill such as they felt more confident, their vocabulary increased, pronunciation they became much better.